Placenta-derived exosomes exacerbate beta cell dysfunction in gestational diabetes mellitus through delivery of miR-320b - Wang, Yanmei; Yuan, Yue; Shen, Shanmei; Ge, Zhijuan; Zhu, Dalong; Bi, Yan (Frontiers in Endocrinology, 2024)
Recent studies have shown placenta-derived exosome (pdE) acts as an important mediator of organ-to-organ interplay regulating maternal metabolic alterations, however, the function and mechanisms of placental exosomes on pancreatic β-cell maladaptation in gestational diabetes mellitus (GDM) remain unclear. The purpose of this investigation was to ascertain how placental exosomes affected the β-cell dysfunction associated with the onset of GDM. Exosomes were isolated from chorionic villi explants of pregnant mice and humans with normal glucose tolerance (NGT) and GDM. The effects of pdE from GDM on glucose tolerance in vivo and islets function in vitro were determined. Isolated islets from mice fed on the chow diet displayed an increase in apoptosis and observed their glucose-stimulated insulin secretion (GSIS) greatly diminished by PdE from GDM mice. Mice that accepted PdE from mice with GDM possessed glucose intolerance.Based on miRNA microarray assay and bioinformatics analysis from human placental exosomes, we identified miR-320b selectively enriched in PdE secreted in GDM compared with NGT. Importantly, the level of placental miR-320b was positively correlated with the 1h-glucose and 2-h glucose of a 75 g oral glucose tolerance test (OGTT) during human pregnancies. Furthermore, miR-320 overexpression attributed to impaired insulin secretion and increased apoptosis in MIN6 cells and islets obtained from mice with normal insulin sensitivity. This study firstly proposed that altered miRNAs in pdE contribute to defective adaptation of β cells during pregnancy, which expands the knowledge of GDM pathogenesis. Exosomes from the placenta may be an emerging therapeutic target for GDM.